Phylogenomic and functional analyses of salmon lice aquaporins uncover the molecular diversity of the superfamily in Arthropoda - Stavang, Jon A.; Chauvigné, François; Kongshaug, Heidi; Cerdà, Joan; Nilsen, Frank; Finn, Roderick N. (BMC Genomics, 2015)
14 pages, 5 figures, electronic supplementary material https://doi.org/10.1186/s12864-015-1814-8 Background: An emerging field in biomedical research is focusing on the roles of aquaporin water channels in parasites that cause debilitating or lethal diseases to their vertebrate hosts. The primary vectorial agents are hematophagous arthropods, including mosquitoes, flies, ticks and lice, however very little is known concerning the functional diversity of aquaporins in non-insect members of the Arthropoda. Here we conducted phylogenomic and functional analyses of aquaporins in the salmon louse, a marine ectoparasitic copepod that feeds on the skin and body fluids of salmonids, and used the primary structures of the isolated channels to uncover the genomic repertoires in Arthropoda. Results: Genomic screening identified 7 aquaporin paralogs in the louse in contrast to 42 in its host the Atlantic salmon. Phylogenetic inference of the louse nucleotides and proteins in relation to orthologs identified in Chelicerata, Myriapoda, Crustacea and Hexapoda revealed that the arthropod aquaporin superfamily can be classified into three major grades (1) classical aquaporins including Big brain (Bib) and Prip-like (PripL) channels (2) aquaglyceroporins (Glp) and (3) unorthodox aquaporins (Aqp12-like). In Hexapoda, two additional subfamilies exist as Drip and a recently classified entomoglyceroporin (Eglp) group. Cloning and remapping the louse cDNAs to the genomic DNA revealed that they are encoded by 1-7 exons, with two of the Glps being expressed as N-terminal splice variants (Glp1_v1, -1_v2, -3_v1, -3_v2). Heterologous expression of the cRNAs in amphibian oocytes demonstrated that PripL transports water and urea, while Bib does not. Glp1_v1, -2, -3_v1 and -3_v2 each transport water, glycerol and urea, while Glp1_v2 and the Aqp12-like channels were retained intracellularly. Transcript abundance analyses revealed expression of each louse paralog at all developmental stages, except for glp1_v1, which is specific to preadult ...